PENGUATAN SAINS MAKHLUK HIDUP MELALUI AJARAN TRI PRAMANA (SABDA, BAYU, IDEP) PADA SISWA KELAS I SEKOLAH DASAR - Gusti Ayu Dewi Setiawati (Guna Widya: Jurnal Pendidikan Hindu, 2024)
Science is an activity that can improve thinking abilities. Science activities allow children to explore various objects, both living objects (living creatures) and non-living objects around them. 1st grade of elementary school students are still young children who need to strengthen their introduction to science about living things. In the teachings of Hinduism there is Tri Pramana which means three powers possessed by living creatures. This research is an descriptive-qualitative research using a literature study method which aims to describe strengthening the introduction of science about living things through the teachings of Tri Pramana (Bayu, Sabda, Idep) in 1st grade of elementary school students. Based on the research results, it was found that strengthening the introduction of science about living things through Tri Pramana teachings for 1 st grade elementary school students is an effort to increase understanding through meaningful learning strategies regarding exploration activities and simple grouping of living things, consisting of plants, animals and humans. The Eka Pramana group are organisms that only have one power in their lives (Bayu), for example plants, the Dwi Pramana group, namely organisms that have two powers in their lives (Bayu, Sabda), for example animals, and the Tri Pramana group, namely organisms that in his life he has three powers (Bayu, Sabda, Idep), an example of which is humans.